Health-Promoting Lifestyle and Eating Behavior Patterns in Pregnant Women: A Cross- Sectional Study - Hajian, Sepideh; Aslani, Armin; Fathnezha-Kazemi, Azita (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: Weight gaining during pregnancy is under the influence of an adopted lifestyle. For planning appropriate interventions to prevent obesity in pregnancy, it is essential to have a better perception of health-promoting behaviors. This study aimed to evaluate Health-promoting lifestyle and eating behavior patterns in pregnant women. Methods: A cross-sectional study was carried out on 360 pregnant women by a multistage cluster sampling method for a period of 6 months from March-August 2017 in Tabriz, Iran. Data were collected by self-reported questionnaires including demographic and obstetric, health-promoting behaviors (HPLPII), and eating behavior patterns questionnaires. Descriptive and inferential statistics, namely Pearson's test were used to evaluate the association between variables. Results: The Mean (SD) total score of health-promoting behaviors in pregnant women was 135.21 (20.03) and maximum and minimum scores were perceived by Spiritual growth 26.84(4.90) and physical activity 16.71(40.14) respectively. In eating behavior patterns, the greatest score was received by eating healthy and low-fat meals and cultural behaviors. According to the Pearson Correlation test, there was a significant inverse relationship between health-promoting behaviors and fast food consumption (P<0/001). Also, a significant direct relation was detected between health-promoting behaviors and the cultural eating pattern. Conclusions: Intermediate scores received in adopting health-promoting behaviors suggest the habits need special attention regarding stress management and physical activity in pregnant women. Despite the tendency to low-fat meals, dietary consultation and informative programs are essential. Also, a comprehensive approach to adopting a healthy lifestyle is required.